Hydroelectric centers in Mexico: past, present and future - Leonardo de Jesús Ramos Gutiérrez; Manuel Montenegro Fragoso (Tecnología y ciencias del agua, 2012)
urces are the most attractive renewable resources given its geography, topography and landforms. It is worth mentioning that since August 14, 1937, when the CFE was created, the country has had 64 hydroelectric plants, 20 of which are significantly large and 44 are small. Fiftyseven hydroelectric plants produce electric energy and 7 are not in operation: El Durazno, Huazuntlán, Ixtapantongo, Santa Bárbara, Las Rosas, Tepazolco and Tingambato. There are a total of 181 generator units of this type. Of the 20 largest plants, 5 are in the Northwest Regional Production District, 2 in the North, 5 in the West, 2 are in the Central Regional Production District and 6 are in the Southeast. Sustainability based on the use of renewal resources should be a guiding principle in Mexico. Countries that have exhausted their hydroelectric potential will attempt to sell their technology and countries such as Mexico will significantly increase the construction of this type of plant because of the great advantages they offer over other energy sources. In the last decades of the 20th century, hydroelectric plants were not built in the country because of the interest in building thermoelectric plants during the middle of that century, which were considered less expensive and thus more economically feasible for public finances. Additionally, natural oilfields found in March 1971, known as Cantarell, led to the government's inclination toward plants that use fossil fuels, freeing up the public finances. Today, this is considered to have been an error, given the environmental problem experienced worldwide.